Identification of a novel fusion transcript between human relaxin-1 (RLN1) and human relaxin-2 (RLN2) in prostate cancer. (15th January 2016) - Tevz, Gregor; McGrath, Sean; Demeter, Ryan; Magrini, Vincent; Jeet, Varinder; Rockstroh, Anja; McPherson, Stephen; Lai, John; Bartonicek, Nenad; An, Jiyuan; Batra, Jyotsna; Dinger, Marcel E.; et al.
Abstract: Simultaneous expression of highly homologous RLN1 and RLN2 genes in prostate impairs their accurate delineation. We used PacBio SMRT sequencing and RNA-Seq in LNCaP cells in order to dissect the expression of RLN1 and RLN2 variants. We identified a novel fusion transcript comprising the RLN1 and RLN2 genes and found evidence of its expression in the normal and prostate cancer tissues. The RLN1-RLN2 fusion putatively encodes RLN2 isoform with the deleted secretory signal peptide. The identification of the fusion transcript provided information to determine unique RLN1-RLN2 fusion and RLN1 regions. The RLN1-RLN2 fusion was co-expressed with RLN1 in LNCaP cells, but the two gene products were inversely regulated by androgens. We showed that RLN1 is underrepresented in common PCa cell lines in comparison to normal and PCa tissue. The current study brings a highly relevant update to the relaxin field, and will encourage further studies of RLN1 and RLN2 in PCa and broader. Highlights: A novel RLN1-RLN2 fusion was observed in LNCaP cells and normal and prostate cancer tissues. The fusion putatively encodes a RLN2 isoform with a deleted secretory signal peptide. RLN1 is underrepresented in PCa cell lines. Androgens inversely regulate RLN1 and the RLN1-RLN2 fusion transcript.